Frequency of Parafunctional Habits and Malocclusion in Patients with Temporomandibular Disorders in Public Dental Hospital - Bukhari, Syed Junaid Hussain; Khan, Shafi Ullah; Babar, Adnan; Somair, Sana; Rehman, Anis Ur; Imran, Ayesha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To correlate the frequency of parafunctional habits and dental malocclusion in patients presenting with and without temporomandibular joint disorders. Study Design: Correlational study. Place and Duration of Study: Department of Oral and Maxillofacial Surgery, Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from Feb to Jul 2024. Methodology: A total of 150 patients with parafunctional habits and dental malocclusion issues were assessed for presence or absence of temporomandibular joint (TMJ) disorders. The assessment for presence or absence of TMJ disorders was done according to standard guidelines furnished by the American Academy of Orofacial Pain, which included TMJ pain, muscle stiffness, and joint noises. Primary variables studied were the frequency of parafunctional habits and malocclusion between patients with and without TMJ disorders. Results: Bruxism was reported in 47(51.1%) versus 12(20.7%) patients (p<0.001), nail biting was reported in 23(25.0%) versus 07(12.1%) patients, (p=0.054), lip biting was reported in 09(9.8%) versus 04(6.9%) patients (p=0.541) holding objects in the mouth was reported in 18(19.6%) versus 05(8.6%) patients (p=0.070) and leaning the face on both arms was seen in 20(21.7%) versus 06(10.3%) patients (p=0.073). Class-I Occlusion was seen in 06(6.5%) versus 36(62.1%) patients, Class-II malocclusion in 55(59.8%) versus 22(37.9%) patients and Class-III malocclusion was seen in 31(33.7%) versus 00(0%) between both groups (p<0.001) Conclusion: We conclude that parafunctional habits and malocclusion are major and important risk factors leading to TMJ disorders in patients.